Rhizobium leguminosarum Biovar viciae 1-Aminocyclopropane-1-Carboxylate Deaminase Promotes Nodulation of Pea Plants - Ma, Wenbo (American Society for Microbiology, 2003)
Ethylene inhibits nodulation in various legumes. In order to investigate strategies employed by Rhizobium to regulate nodulation, the 1-aminocyclopropane-1-carboxylate (ACC) deaminase gene was isolated and characterized from one of the ACC deaminase-producing rhizobia, Rhizobium leguminosarum bv. viciae 128C53K. ACC deaminase degrades ACC, the immediate precursor of ethylene in higher plants. Through the action of this enzyme, ACC deaminase-containing bacteria can reduce ethylene biosynthesis in plants. Insertion mutants with mutations in the rhizobial ACC deaminase gene (acdS) and its regulatory gene, a leucine-responsive regulatory protein-like gene (lrpL), were constructed and tested to determine their abilities to nodulate Pisum sativum L. cv. Sparkle (pea). Both mutants, neither of which synthesized ACC deaminase, showed decreased nodulation efficiency compared to that of the parental strain. Our results suggest that ACC deaminase in R. leguminosarum bv. viciae 128C53K enhances the nodulation of P. sativum L. cv. Sparkle, likely by modulating ethylene levels in the plant roots during the early stages of nodule development. ACC deaminase might be the second described strategy utilized by Rhizobium to promote nodulation by adjusting ethylene levels in legumes.